(untitled) (Turkish Journal of Computer and Mathematics Education (TURCOMAT), 2019)
Digital Watermarking with PSO and Fuzzy Logic is an attempt to find suitable location using PSO and Fuzzy Logic by looking at the surrounding pixels and adaptively adjusting the pixel intensity values to encode the watermark bits. The result obtained in this technique indicate that following adaptive insertion on the pixels after finding location by PSO is even more effective to obtain better fidelity and robustness. The inverse tradeoff between robustness and fidelity is also demising. The method proposed includes color watermarking as an extension of gray scale watermarking by dividing color image into RGB gray scale and then uniting them together.